Evaluating the role of protection motivation theory in information security policy compliance: Insights from the banking sector using PLS-SEM approach - Alrawhani, Ebrahim Mohammed; Awanis, Romli; Al-Sharafi, Mohammed A. (MDPI, 2025)
This research investigated the behavior related to compliance with information security policy in the Yemeni banking sector by using the protection motivation theory (PMT). While PMT has been a prominent framework in understanding information security compliance, previous research has produced inconsistent findings regarding its factors' effects on compliance behavior, necessitating further empirical validation. Moreover, the majority of research has been carried out in developed countries. The data were collected from 210 bank employees in Yemen and analyzed using PLS-SEM. This research study showed that perceived self-efficacy, response efficacy, and severity significantly influence the employees' intentional behavior in complying with information security policies. However, the results did not support the hypotheses of perceived response cost and perceived vulnerability. The study also discusses both theoretical and practical implications of enhancing information security compliance behavior.